Neutron pumping of active medium formed by gadolinium isotopes 155Gd and 156Gd pair: A feasibility study; Applied Radiation and Isotopes; Vol. 206 - Bedenko S. V. Sergey Vladimirovich; Polozkov S. D. Sergey Dmitrievich; Demin A. S. Aleksey Sergeevich; Ghal-Eh N. Nima; Rahmani F. Faezeh; Vega-Carrillo H. R. Hector Rene (2024, 2024)
Title screen